Clinical and molecular characteristics of 168 probands and 65 relatives with a clinical presentation of classical Ehlers–Danlos syndrome. Issue 10 (26th July 2021) - Colman, Marlies; Syx, Delfien; De Wandele, Inge; Dhooge, Tibbe; Symoens, Sofie; Malfait, Fransiska
Abstract: Classical Ehlers–Danlos syndrome (cEDS) is a heritable connective tissue disorder mainly caused by pathogenic variants in COL5A1 or COL5A2, encoding type V collagen. Its diagnosis, based on clinical criteria and molecular confirmation, can be challenging. We report the molecular and clinical characteristics of 168 probands (72 clinically evaluated at our center) and 65 relatives with a clinical presentation of cEDS. Type V collagen defects were found in 145 probands, 121 (83.5%) were located in COL5A1 and 24 (16.5%) in COL5A2 . Although 85.6% of molecularly confirmed patients presented the two major clinical criteria (generalized joint hypermobility, hyperextensible skin with atrophic scarring), significant inter‐ and intrafamilial phenotypic variability was noted. COL5A2 variants often caused a more severe phenotype. Vascular complications were rare in individuals with type V collagen defects (1.4%). Among the 72 probands clinically evaluated in our center, the mutation detection rate was 82.0%. The majority (68.1%) harbored COL5A1 / COL5A2 defects. Yet, 13.9% harbored a defect in another gene ( COL1A1, PLOD1, TNXB, AEBP1 ) highlighting important clinical overlap and the need for molecular confirmation of the diagnosis as this has implications regarding follow‐up and genetic counseling. Eighteen percent of the 72 probands remained molecularly unexplained and a COL5A1 variant of unknown significance was identified in 6.9%.